Factors associated with successful weight loss after liraglutide treatment for obesity. Issue 2 (24th October 2022) - Sannaa, Wassel; Dilmaghani, Saam; BouSaba, Joelle; Maselli, Daniel; Atieh, Jessica; Eckert, Deborah; Taylor, Ann L.; Harmsen, W. Scott; Acosta, Andres; Camilleri, Michael
Abstract: Aim: To identify patient factors, including gastrointestinal functions, that are predictive or associated with weight loss in response to once‐daily 3 mg liraglutide administered subcutaneously (SQ) or placebo in obesity. Methods: One hundred and thirty‐six obese adults (87% female) were randomized in a placebo‐controlled, 16‐week trial of liraglutide, escalated to 3 mg administered SQ daily. Gastrointestinal functions were measured at baseline and 16 weeks: gastric emptying of solids (GET1/2 ); fasting and postprandial gastric volumes; kcal ingested during ad libitum buffet meal and the nutrient drink test. GET1/2 was also measured at 5 weeks. A multiple variable regression model examined variables associated with weight loss of more than 4 kg at 16 weeks. A parsimonious model using backward selection identified the final model. Results: Weight loss of more than 4 kg at 16 weeks occurred in 71% of liraglutide‐ and 16% of placebo‐treated patients. In all participants combined, parameters univariately associated with a weight loss of more than 4 kg were GET1/2 at 5 and 16 weeks, weight loss at 5 weeks and kcal intake during the buffet meal at 16 weeks. The final parsimonious model (area under the receiver operator characteristics [AUROC] curve = 0.832) identified that factors associated with more than 4‐kg weight loss were GET1/2 at 5 weeks (OR = 2.505; 95% CI: 1.57‐3.997) per 50 minutes and kcal intake during ad libitum meal at 16 weeks (OR = 0.721; 95% CI: 0.602‐0.864) per 100 kcal. Among only the 60 liraglutide‐treated subjects, kcal intake at 16 weeks was associated with 4‐kg weight loss (AUROC = 0.757). Conclusions: Slower GET1/2 and weight loss at 5 weeks predicted a weight loss of more than 4 kg at 16 weeks in all participants. Among liraglutide‐treated adults, weight loss of more than 4 kg was associated with ad libitum meal kcal intake at 16 weeks.